Analysis of Main and Healthy Phenolic Compounds in Foods. (3rd December 2019) - Delgado, Amélia Martins; Issaoui, Manel; Chammem, Nadia
Abstract: Background: In the last few decades, the media has been overwhelming the consumer with various dietary requirements that some of which lead to no avail. On the other hand, the Mediterranean diet, which stems from a very ancient lore, stands as one of the most effective diets whose conspicuous and positive results are still impacting the lives of many Mediterranean locals. The "Mediterranean Diet" is an umbrella term that is used to denote a plethora of natural ingredients used in the culinary tradition of the region, and which comprises but is not limited to olive oil, cereals, wine, fruits, dried fruits, and spices. MD components are known for being rich in antioxidant compounds. Polyphenols belong to the category of antioxidants that occur in the above-mentioned Mediterranean foods. Objective: The current review aims at presenting main classes of phenols from plant foods, their role as dietary components, and an overview on analytical methods for their extraction from food matrices, their separation, detection and quantification. Conclusions: The discrimination of phenols is not an easy matter, and several methods are described in the literature, mainly chromatographic methods, which are herein reviewed. In short, phenols are mainly found in vegetable foods in which the Mediterranean Diet is rich. The health effects of some phenols and analytical methods are herein revised. Highlights: Phenols or Phenolics is a designation corresponding to compounds that have one or more hydroxyl groups attached to a 6-carbon aromatic ring. Phenols in foods occur mainly as secondary metabolites of vegetables, often found in polymeric forms (polyphenols). Phenols from foods are mainly simple phenols (e.g., caffeic acid), flavonoids, the most varied and ubiquitous class (e.g., catechin, quercetin), stilbenes (resveratrol), lignans, and tannins. In addition to the wide range of polyphenols present in foods, the compounds are quantitatively and qualitatively distributed in a heterogenous way in the different compartments of the food matrix. This structural and compartmental diversity leads to an important variability of the physicochemical properties impacting otherwise the extraction of phenols. Total phenols are determined by the Folin Cioucalteau method, as described in European Pharmacopeaea.